Guidelines for multimodality radiological staging of lung cancer - Shukri Loutfi; Azzam Khankan; Sarah Al Ghanim (Elsevier, 2012)
Summary: Lung cancer is among the most common type of cancers and is a leading cause of cancer-related deaths with smoking representing the leading risk factor.It is classified into non-small cell lung cancer (NSCLC) representing 70-80% of cases and small cell lung cancer (SCLC) which has neuroendocrine properties with poor outcome.Staging of NSCLC is based on the TNM classification system while SCLC was usually classified into limited and extensive disease, though the use of TNM staging system for SCLC is recommended.Imaging studies are used to determine the pre-operative staging of lung cancer. Accurate radiological staging is essential to determine tumor resectability as well as to avoid futile surgeries and to assess patient's outcome. Moreover, radiological examinations are used for the evaluation of tumor response to treatment.This manuscript will review the utilization of imaging studies in the management of lung cancer based on the most recent guidelines by the National Comprehensive Cancer Network (NCCN). Keywords: Lung Cancer, Staging, Guidelines